Emission Rate Estimates of Methane and Carbon Dioxide at Several Sectors in New York State in 2021 - Alexandra Catena; Mackenzie Smith (PANGAEA, 2025)
Aircraft measurements of methane and carbon dioxide mixing ratios were carried out by Champion X at several facilities in New York State in 2021. This dataset includes the calculated emission rates and uncertainties from each of the sampled facilites. The emission rate data includes all estimated CH4 and CO2 emission rates calculated by Champion X using a mass balance approach. It also includes the number of laps, wind direction (deg) and speed (m/s), start and end time, lowest and highest altitude measured (m), surface fraction, mean radius of the loop around the facility (m), temperature (C), and latitude and longitude coordinates. Measurements were made using a single-engine Mooney aircraft where ambient air was drawn in through the rearward-facing inlets mounted on the wing of the aircraft. In situ methane, carbon dioxide, and water vapor were recorded using a Picarro G2401 cavity ring down spectrometer at 1 Hz with calibrations done in-flight. Horizontal wind speed and direction are calculated following the method outlined in Conley et al. (2014), which combines pitot-static pressure airspeed measurement with GPS-calculated aircraft heading and ground speed. Meteorological parameters were measured using a Vaisala HMP60 probe and geographical coordinates recorded through a Hemisphere high-precision differential GPS. Further descriptions of the aircraft, analyzer precision and accuracy, and met data can be found elsewhere (Conley et al., 2017; Karion et al., 2015; Peischl et al., 2016; Ravikumar et al., 2024; Smith et al., 2015).